S Sikap Tenaga Kefarmasian dalam Penggalian Informasi Pada Swamedikasi Nyeri Gigi di Apotek-Apotek Kota Pekanbaru Provinsi Riau: Sikap Tenaga Kefarmasian dalam Penggalian Informasi Pada Swamedikasi Nyeri Gigi di Apotek-Apotek Kota Pekanbaru Provinsi Riau - Septi Muharni reviewer (Jurnal Penelitian Farmasi Indonesia, 2016)
The stages of swamedication services include patient assessment, which is a patient assessment called information excavation. Information excavation is intended to assess patients who have carried out safety assessment, accuracy and rationality swamedikasi by patients. The purpose of this study is to determine the description of attitudes of pharmaceutical personnel in obtaining information about toothache at pharmacists Pekanbaru. This research is a descriptive observational study with a sampling method that consists of systematic random sampling of 100 people from pharmaceutical manpower. From the research that was done the number of staff found pharmacist assistants who perform the extracting information as much as 63%, the percentage score of extracting information obtained 19.25% with a gesture interpretation is lacking, while the number of pharmaceutical technical personnel that it Extracting information as much as 37%, the percentage of score to be obtained from information obtained 30.7% with less attitude and interpretation there are pharmacists who perform services swamedikasi extracting information about the dental pain. The total percentage of information extraction by the staff found pharmacist assistants and pharmaceutical technical personnel as 23.5% with less interpretation of the posture